IRON HAND : Smashing the Enemy's Air Defences - Thornborough, Anthony M.; Mormillo, Frank B.; Cassanova, Tony; Jackson, Kevin (Patrick Stephens Limited, 2002)
Learn how military pilots protect themselves against an attack from a surface-to-air missile (SAM). This book describes the evolution of American anti-radar weapons, related jamming tactics and stealth technology as leading-edge countermeasures to the SAM and other sophisticated ground-based anti-aircraft defenses. The focus is on new weapons and tactics as they emerged in combat, beginning with the Vietnam War and later the Persian Gulf and Balkans conflicts. The text combines an analytical overview of the weapons systems mixed with first-hand anecdotal reminiscences from former air and ground crews